Extension Contacts: Definitions and Examples for Unifas - Bryan D. Terry; Glenn D. Israel (EDIS)
AEC-377, an 8-page fact sheet by Bryan D. Terry and Glenn D. Israel, describes how UF/IFAS' Unifas software should be used to report Extension contacts, defines two types of contacts (Extension and Clientele) and provides examples for recording contacts. Published by the UF Department of Agricultural Education and Communication, May 2006.